Komunikasi Politik Partai Politik dalam Pemilu: Studi Kasus Strategi Komunikasi Politik Dewan Pimpinan Daerah (DPD) Partai Golkar - Farida Laela (Syntax Corporation, 2023)
This study aims to examine the political communication strategy carried out by the Golkar party in increasing votes in the 2019 legislative election in Bogor Regency. This research uses qualitative methods by determining resource persons by purposive sampling which aims to obtain specific and accurate information directly from the source. In addition, the ideological function of parties and contestation in elections motivated by the characteristics possessed by legislative candidates or candidates in playing their role increasingly adds variety to the electoral competition. The conclusion, first, is regarding the positioning of the Golkar party in the policy-making process and political constellation in Bogor Regency. There are four factors that determine the positioning of the Golkar party in Bogor Regency in relation to the political communication process they run, including: first, figures who process in the Golkar party so that they become populist figures.